Serotype Distribution, Antimicrobial Resistance, and Class 1 Integrons Profiles of Salmonella from Animals in Slaughterhouses in Shandong Province, China - Zhao, Xiaonan; Ye, Chaoqun; Chang, Weishan; Sun, Shuhong (Frontiers in Microbiology, 2017)
The current study aimed to analyze the prevalence and characterization of Salmonella enterica isolated from animals in slaughterhouses before slaughter. A total of 143 non-duplicate Salmonella were recovered from 1,000 fresh fecal swabs collected from four major pig slaughterhouses (49/600, 8.2%) and four major chicken slaughterhouses (94/400, 23.5%) between March and July 2016. Among Salmonella isolates from pigs, the predominant serovars were Salmonella Rissen (28/49, 57.1%) and Typhimurium (14/49, 28.6%), and high antimicrobial resistance rates were observed for tetracycline (44/49, 89.8%) and ampicillin (16/49, 32.7%). Class 1 integrons were detected in 10.2% (5/49) of these isolates and all contained gene cassettes aadA2 (0.65 kb). Two β-lactamase genes were detected among these isolates, and most of these isolates carried blaTEM-1 (46/49), followed by blaOXA-1(4/49). Seven STs (MLST/ST, multilocus sequence typing) were detected in these isolates, and the predominant type was ST469 (19.6%). Among Salmonella isolates from chickens, the predominant serovars were Salmonella Indiana (67/94, 71.3%) and Enteritidis (23/94, 24.5%), and high antimicrobial resistance rates were observed for nalidixic acid (89/94, 94.7%), ampicillin (88/94, 93.6%) and tetracycline (81/94, 86.2%). Class 1 integrons were detected in 23 isolates (23/94, 24.5%), which contained empty integrons (0.15 kb, n = 6) or gene cassettes drfA17-aadA5 (1.7 kb, n = 6), aadA2 (1.2 kb, n = 5), drfA16-blaPSE-1-aadA2-ereA2 (1.6 kb, n = 5) or drfA1-aadA1 (1.4 kb, n = 1). Three β-lactamase genes were detected, and all 94 isolates carried blaTEM-1, followed by blaCTX-M-55 (n = 19) and blaSPE−1 (n = 3). Five STs were found in these isolates, and the predominant type was ST17 (71.3%). Our findings indicated that Salmonella was widespread in animals at slaughter and may be transmitted from animal to fork.